Cost-effectiveness analysis of endovascular coiling and neurosurgical clipping for aneurysmal subarachnoid hemorrhage in Thailand. (20th September 2021) - Duangthongphon, Pichayen; Kitkhuandee, Amnat; Munkong, Waranon; Limwattananon, Phumtham; Waleekhachonloet, Onanong; Rattanachotphanit, Thananan; Limwattananon, Supon
Abstract : Background: For patients with aneurysmal subarachnoid hemorrhage (aSAH), the Universal Coverage Scheme in Thailand covers the full costs of surgical and endovascular procedures except for those of embolization coils and assisting devices. Costs and effectiveness were compared between endovascular coiling and neurosurgical clipping to inform reimbursement policy decisions. Methods: Costs and quality-adjusted life years (QALYs) were compared between coiling and clipping using the decision tree and Markov models. Mortality and functional outcomes of clipping were derived from national and hospital databases, and relative efficacies of coiling were obtained from meta-analyses of randomized controlled trials. Risks of rebleeding were abstracted from the International Subarachnoid Aneurysm Trial. Costs of the primary treatments, retreatments and follow-up care as well as utilities were obtained from hospital-based data. Non-health and indirect costs were abstracted from standard cost lists. Results: Coiling and clipping contributed 10.59 and 9.28 QALYs to patients aged in their 50s. Under the societal and healthcare perspectives, the incremental costs incurred by coiling compared with clipping were US$1923 and $4343, respectively, which were equal to the incremental cost-effectiveness ratio of US$1470 and $3321 per QALY gained, respectively. Coiling became a cost-saving option when the costs of coil devices were reduced by 65.7%. At the country's cost-effectiveness threshold of US$5156, the probability of coiling being cost-effective was 71.3% and 65.6%, under the societal and healthcare perspectives, respectively. Conclusion: Endovascular treatment for aSAH is cost-effective and this evidence supports coverage by national insurance.